Jerzy Stempowski On Józef Wittlin’s Salt of the Earth - Chabiera, Magdalena (Colloquia Litteraria, 2019)
In a 1936 text dedicated to Józef Wittlin’s novel Jerzy Stempowski tries to position it within the context of the contemporary political, social and cultural events. He also analyses the artistic values of the novel in relation to the changes of the world-view caused by the traumatic events of the First World War.